The effects of diaphenylsulfone (DDS) against chloroquine-resistant Plasmodium falciparum - Degowin, Richard L. (1966)
In view of the problems caused by the chloroquine-resistance of some strains of Plasmodium falciparum, the authors have investigated the effectiveness of diaphenylsulfone against two such resistant strains, from Malaya and Viet-Nam. They found that diaphenylsulfone given during acute attacks of malaria had a blood schizontocidal activity against the Malayan resistant strain but was not rapidly effective in terminating acute attacks in non-immune persons, and that, when the drug was given prophylactically in relatively small doses, it was substantially effective in preventing patency of mosquito-induced infection with the same strain. The protective effect of diaphenylsulfone is that of a clinical prophylactic or suppressive drug; it does not appear to be a true causal prophylactic. It was also found that the protective effect is vitiated by the concurrent administration of paraaminobenzoic acid. These studies indicate a need for further assessment of the antimalarial value of sulfones and sulfonamides, both alone and in combination with other drugs, for prevention and cure.